Pemodelan Binis Sistem dan Teknologi Informasi Pada Lembaga Keuangan Berbasis Urun Dana - Rio Yunanto (Labkat Press KA FTIK UNIKOM, 2018)
Various types of financial institutions, especially for the non bank must be handle carefully because it has the role of strategic in economic development a country. Financial institutions, with the support system of information technology is often abbreviated STI the potential to be growing up fast and able to provide communications access to the remote areas in Indonesia. Crowdfunding is a phenomenon fundrasing that has the potential is huge if managed well. Financial institutions are based on crowdfunding now rely on STI as the backbone of operational technical. Internet make it easier for information a fundraiser across the massive and broad. Its able to give persuasive quickly to anyone and anytime. STI is also able to provide support assistance and supervision of the clients or business enteties received funding. Various parties can be involved in assistance the process of funding so that activities crowdfunding become more transparent and more accountable. Modeling business STI in financial institutions based crowdfunding to be very strategic considering the role of STI a very dominant. Modeling is expected to encourage the use of STI the maximum to support the role of financial institutions based on crowdfunding as one of the economy a country.